การพัฒนาทักษะการเขียนคำสะกดคำยากโดยใช้ชุดแบบฝึกทักษะการเขียนสะกดคำของนักเรียนระดับประถมศึกษา โรงเรียนบ้านโนนประทาย อำเภอกุดชุม จังหวัดยโสธร - เวฬุวนารักษ์, นุชจรี; สองเมือง, ณัฏฐ์พิชญา; (ศิลากุล), พระมหานพรัตน์ ขนฺติธมฺโม (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 2 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 2 : พฤษภาคม - สิงหาคม 2567, 2024)
This research aims to study the level of difficult word spelling skills, create practice exercises for spelling difficult words, and compare the learning achievement of elementary school students at Nonprathai school before and after using these exercises in the academic year 2022, based on the 80/80 criterion. A sample group of 28 students was randomly selected. The research instruments included difficult word spelling exercises, a Thai language knowledge management plan, and an achievement test. The data were analyzed using percentage, mean, standard deviation, and hypothesis testing with a t-test. The research findings indicated that the students' difficult word spelling skills were at a moderate level. The difficult word spelling exercises showed an efficiency of 81.20/82.05, meeting the set criteria. Furthermore, the students’ learning achievement after using the exercises showed a statistically significant improvement at the .05 level.